In Search for a Method of Sociology. Georg Simmel and the Boundaries of Metropolitan Reality - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2007)
Review: Georg Simmel. 2007. Sociologija ir kultūros filosofija. Vilnius: Margi raštai.